2007
DOI: 10.1002/adfm.200600598
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Sorption and Electrical Response of Au‐Nanoparticle– Dendrimer Composites

Abstract: Films comprising Au nanoparticles and polyphenylene dendrimers (first and second generation) are deposited onto transducer substrates via layer‐by‐layer self‐assembly and characterized by atomic force microscopy and X‐ray photoelectron spectroscopy. Their sorption behavior is studied by measuring the uptake of solvents from the vapor phase with quartz crystal microbalances (QCMs). The resistance of the films is simultaneously monitored. Both sensor types, QCMs and chemiresistors, give qualitatively very simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 44 publications
1
77
0
Order By: Relevance
“…[7] Combining this model with Ohms' law gives the following equation for the differential change in resistance: [15,17] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Combining this model with Ohms' law gives the following equation for the differential change in resistance: [15,17] …”
Section: Resultsmentioning
confidence: 99%
“…Based on this pioneering work significant progress has been made toward the application of nanoparticle assemblies in electronic devices, especially, as sensitive coatings for chemical sensors. [12][13][14][15][16][17] The strong dependence of the conductivity of metalnanoparticle assemblies on the interparticle distances establishes a base for their potential application as strain sensors.…”
Section: Introductionmentioning
confidence: 99%
“…12,23 The implementation of the sensors should be simple and cost-effective enough to be economically viable for real-world applications. Sensors with electronic and electro-acoustic transduction mechanisms, such as chemically sensitive resistors [24][25][26][27][28][29][30][31][32][33] and quartz-crystal microbalance (QCM) sensors [34][35][36] are among the most attractive and widespread elements for sensing applications that involve the detection and classification of volatile organic compounds (VOCs) in the gas phase. 9,11,13,16,19,20,24,37 Recently, we have shown that polycyclic aromatic hydrocarbon (PAH) derivatives as sensing materials in chemiresistors, field effect transistors or QCM sensors can provide good sensitivity and robust selectivity towards different polar and nonpolar VOCs, while being highly tolerant even to drastic humidity variations.…”
Section: Introductionmentioning
confidence: 99%
“…Vosmayer et al have shown that composites of dendrimer-AuNP are effective for sensing vapors of various solvents in a chemiresistor device. [32][33][34] Using our current system, we used the optical response of the materials to transduce the responsiveness of the composite films to various solvent systems. Immersion of a Den G4 -NP film (4:1 ratio) in 0.1 mM acetic acid, pure water, 0.1 mM ammonium hydroxide, methanol, and hexane resulted in differential swelling of the films with a concomitant shift of the SPR band ( Fig.…”
mentioning
confidence: 99%